PENGARUH PEMBERIAN EKSTRAK BROKOLI (Brassica Olaracea L. Var Italica) TERHADAP MORFOLOGI SPERMATOZOA PADA MENCIT (Mus musculus) YANG DIPAPAR TIMBAL SCOPING REVIEW - Baina Safira Naldi (2022)
Air pollution is still a problem in Jakarta and other big cities. One of the pollutant substances that is harmful to living thing is lead which can cause abnormality in the morphology of spermatozoa. This situation can be treated with herbalic ingredients such as broccoli. The purpose of this study was to determine the effectiveness of broccoli extract and the effective dose on the morphology of spermatozoa in mice exposed to lead. This study used scoping review to seek and analyze experimental research journals in both national and international. 4 journals were obtained that match the inclusion and exclusion criteria which contain 3 national and 1 international journals. The results showed that at least 2000mg/kgBW dose of broccoli proven effective in treating abnormality of spermatozoa morphology in mice exposed to lead.